"Am I cut out for this?" Understanding the experience of doubt among first-year medical students. (2nd December 2015) - Liu, Rhianon; Carrese, Joseph; Colbert-Getz, Jorie; Geller, Gail; Shochet, Robert
Abstract: Purpose : Existing research shows that medical students experience high levels of distress. The purpose of this study was to understand how medical students experience doubt, and how doubt relates to distress. Methods : A mixed-methods study was conducted among first-year students at the Johns Hopkins University School of Medicine in June 2012. Students answered survey questions and participated in focus groups about doubt and other forms of distress. Results : Ninety-four percent (112) of students responded to the survey, with 49% reporting a moderate or high degree of doubt. Compared to those reporting no or low doubt, students with moderate/high doubt were significantly more likely to question their purpose and identity, struggle to cope with doubt, and experience depression and emotional hardening. Twenty-eight percent of students (34/112) participated in focus groups to explore their doubt, and three themes emerged: types of doubt, ways of coping with doubt, and impact of doubt. Conclusions : Doubt is highly prevalent among first-year medical students, affects their identity and purpose, and has positive and negative consequences. Doubt among medical students merits awareness and further study, as it may be an important mediator of students' emerging identity and sense of well-being.